Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1990
DOI: 10.1007/bf02722273
|View full text |Cite
|
Sign up to set email alerts
|

A clinical profile of mitral valve prolapse syndrome

Abstract: Clinical, radiologic, electrocardiographic and 2-dimensional echocardiographic findings of fifty cases of mitral valve prolapse syndrome attending the Pediatric Cardiology clinic of I.C.H. and Childrens Hospital, Medical College, Kottayam over a period of ten years from 1980-1989 are presented. Mitral valve prolapse syndrome (MVPS) accounted for 2% of cardiac problems attending our pediatric cardiology clinic. Isolated MVPS constituted 64% of the cases. The common causes of secondary MVPS were Marfan Syndrome-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…Calcd. for C 17 A mixture of 2 (2.83 g, 10 mmol) and benzoylacetonitrile (1.45 g, 10 mmol) in ethanol (20 mL) and few drops of piperidine was refluxed for 3 hours. The reaction mixture was left to cool at room temperature.…”
Section: -Aminomentioning
confidence: 99%
See 1 more Smart Citation
“…Calcd. for C 17 A mixture of 2 (2.83 g, 10 mmol) and benzoylacetonitrile (1.45 g, 10 mmol) in ethanol (20 mL) and few drops of piperidine was refluxed for 3 hours. The reaction mixture was left to cool at room temperature.…”
Section: -Aminomentioning
confidence: 99%
“…A review of literature revealed that reaction of aminonitrile derivatives with isothiocyanates gave a variety of product depending on the experimental conditions [17,18]. Thus, treatment of compound 2 with phenyl isothiocyanates in refluxing pyridine, a crystalline brown colored product was formed.…”
mentioning
confidence: 99%
“…Pandit and Choudhary 10 found nearly 81% of patients were from lower socioeconomic class of IV and V, as per B G Prasad classification. Sukumaran et al, 13 and Chadha and Bhagi 8 observed in their studies all patients (100%) and 82% were from the lower socioeconomic stratum, respectively. Hence, low socioeconomic status was identified as one of the consistent characteristics of TB in all the studies in the present one.…”
Section: Discussionmentioning
confidence: 80%